Biodegradable near-infrared-photoresponsive shape memory implants based on black phosphorus nanofillers. (May 2018) - Xie, Hanhan; Shao, Jundong; Ma, Yufei; Wang, Jiahong; Huang, Hao; Yang, Na; Wang, Huaiyu; Ruan, Changshun; Luo, Yanfeng; Wang, Qu-Quan; Chu, Paul K.; Yu, Xue-Feng
Abstract: In this paper, we propose a new shape memory polymer (SMP) composite with excellent near-infrared (NIR)-photoresponsive shape memory performance and biodegradability. The composite is fabricated by using piperazine-based polyurethane (PU) as thermo-responsive SMP incorporated with black-phosphorus (BP) sheets as NIR photothermal nanofillers. Under 808 nm light irradiation, the incorporated BP sheets with concentration of only 0.08 wt% enable rapid temperature increase over the glass temperature of PU and trigger the shape change of the composite with shape recovery rate of ∼100%. The in vitro and in vivo toxicity examinations demonstrate the good biocompatibility of the PU/BP composite, and it degrades naturally into non-toxic carbon dioxide and water from PU and non-toxic phosphate from BP. By implanting PU/BP columns into back subcutis and vagina of mice, they exhibit excellent shape memory activity to change their shape quickly under moderate 808 nm light irradiaiton. Such SMP composite enable the development of intelligent implantable devices, which can be easily controlled by the remote NIR light and degrade gradually after performing the designed functions in the body.